A Systematic Literature Review of Dorsal Root Ganglion Neurostimulation for the Treatment of Pain. Issue 8 (17th August 2020) - Deer, Timothy R; Hunter, Corey W; Mehta, Pankaj; Sayed, Dawood; Grider, Jay S; Lamer, Tim J; Pope, Jason E; Falowski, Steven; Provenzano, David A; Esposito, Michael F; Slavin, Konstantin V; Baranidharan, Ganesan; et al.
Abstract: Objective: To conduct a systematic literature review of dorsal root ganglion (DRG) stimulation for pain. Design: Grade the evidence for DRG stimulation. Methods: An international, interdisciplinary work group conducted a literature search for DRG stimulation. Abstracts were reviewed to select studies for grading. General inclusion criteria were prospective trials (randomized controlled trials and observational studies) that were not part of a larger or previously reported group. Excluded studies were retrospective, too small, or existed only as abstracts. Studies were graded using the modified Interventional Pain Management Techniques–Quality Appraisal of Reliability and Risk of Bias Assessment, the Cochrane Collaborations Risk of Bias assessment, and the US Preventative Services Task Force level-of-evidence criteria. Results: DRG stimulation has Level II evidence (moderate) based upon one high-quality pivotal randomized controlled trial and two lower-quality studies. Conclusions: Moderate-level evidence supports DRG stimulation for treating chronic focal neuropathic pain and complex regional pain syndrome.